Dampak Kebijakan Peraturan Daerah Nomor 8 Tahun 2020 Tentang Rencana Tata Ruang Wilayah (RTRW) Di Kabupaten Kepulauan Meranti - Nurfitasari, Mimi; Hamidi, M.Rasyid; Thariq Hawari, Rafi (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2025)
The policy of prohibiting the planting of commodities that absorb large amounts of water is a strategic step taken by the local government in order to control the rate of environmental damage. This research aims to: 1. Knowing people's perceptions related to Regional Regulation (PERDA) Number 8 of 2020 concerning the Regional Spatial Plan of the Meranti Islands Regency RTRW, and 2. Analyzing the socio-economic impact of PERDA RTRW concerning the Regional Spatial Plan of the Meranti Islands Regency RTRW. This research used a qualitative descriptive method with data collection techniques through surveys and interviews and data analysis using Likert Summated Rating (LSR). The results of the study found that 1) 46.66 percent of people agree with the existence of PERDA RTRW concerning the Regional Spatial Plan of the Meranti Islands Regency RTRW, because it is able to protect the environment from damage arising from oil palm planting in the Meranti Islands Regency area. While 30.00 percent of the community chose strongly disagree with the existence of this policy because it was considered an obstacle to grow and rise from the economic downturn in the coastal area 2). The social impact of this policy is 46.66 percent of the community stated that the existence of this policy has caused differences in views between residents, especially the pros and cons of the prohibition of oil palm planting. Changes in social structure occur when community groups are divided into those who are adaptive to policies and those who are economically marginalized. The economic impact of the ban on oil palm planting in the Meranti Islands Regency area is that 50 percent of the community experienced a decrease in income potential because they could not continue their plans to plant oil palm. The palm oil ban eliminates the potential for new livelihoods that are considered promising.